α,β hybrid peptides: A polypeptide helix with a central segment containing two consecutive β-amino acid residues - Roy, Rituparna S. (National Academy of Sciences, 2004)
Conformational studies on the synthetic 11-aa peptide t-butoxycarbonyl (Boc)-Val-Ala-Phe-α-aminoisobutyric acid (Aib)-(R)-β(3)-homovaline (βVal)-(S)-β(3)-homophenylalanine (βPhe)-Aib-Val-Ala-Phe-Aib-methyl ester (OMe) (peptide 1; βVal and βPhe are β amino acids generated by homologation of the corresponding l-residues) establish that insertion of two consecutive β residues into a polypeptide helix can be accomplished without significant structural distortion. Crystal-structure analysis reveals a continuous helical conformation encompassing the segment of residues 2–10 of peptide 1. At the site of insertion of the ββ segment, helical hydrogen-bonded rings are expanded. A C(15) hydrogen bond for the αββ segment and two C(14) hydrogen bonds for the ααβ or βαα segments have been characterized. The following conformational angles were determined from the crystal structure for the β residues: βVal-5 (φ = –126°, θ = 76°, and ψ = –124) and βPhe-6 (φ =–88°, θ = 80°, and ψ =–118). The N terminus of the peptide is partially unfolded in crystals. The 500-MHz (1)H-NMR studies establish a continuous helix over the entire length of the peptide in CDCl(3) solution, as evidenced by diagnostic nuclear Overhauser effects. The presence of seven intramolecular hydrogen bonds is also established by using solvent dependence of NH chemical shifts.